Effect of disorder on the magnetic properties of LaMn0.5Fe0.5O3 - Bhame, Shekhar D.; Joly, V. L. Joseph; Joy, Pattayil Alias (Physical Review B, 2005)
Polycrystalline LaMn0.5Fe0.5O3 is synthesized by a low-temperature method and the magnetic properties of the resulting powder have been studied after annealing the sample in air at different temperatures in the range 200 degrees C-1350 degrees C. Room temperature Mossbauer spectroscopic studies show that the Fe ions are present in the +3 oxidation state in the material. However, the magnetic properties vary widely in an unexpected manner when samples are annealed at different temperatures. Zero field cooled magnetization studies show a cusp below 100 K, for the sample annealed at 200 degrees C, indicating a spin-glass-like or superparamagnetic behavior. However, this cusp disappears completely when the sample is annealed at 700 degrees C but still showing a magnetic hysteresis loop with reduced magnetization at low temperatures. The cusp again appears when the sample is annealed at higher temperatures with increasing low-temperature magnetization. EPR and IR spectroscopic studies indicate changes in the distribution of Mn3+ and Fe3+ ions in the lattice. The overall results can be explained in terms of random distribution of Mn3+ and Fe3+ ions in the lattice and formation of some magnetic clusters, with the degree of distribution of the ions varying for samples annealed at different temperatures.